Pengaruh Metode Pembelajaran dan Gaya Belajar terhadap Hasil Belajar Siswa MI Roudlotul Mustashlihin Masangan Kulon Sukodono Sidoarjo - Fendi Pratama Putra; Didit Darmawan (Journal on Education, 2024)
In the era of globalization, where change occurs so quickly and competition is increasingly fierce, education becomes a vital means of preparing individuals to face future challenges. This research aims to analyze the influence of learning methods and learning styles on student learning outcomes at MI Roudlotul Mustashlihin Masangan Kulon, Sukodono, Sidoarjo. The population of this study includes all students at MI Roudlotul Mustashlihin Masangan Kulon, Sukodono, Sidoarjo with a total of 488 students. The samples taken were 31 students. This research includes quantitative research. Learning methods and learning styles are measured as independent variables, while student learning outcomes are measured as dependent variables. Data analysis uses the regression method to determine the extent of the influence of the independent variable on the dependent variable. The findings of this research indicate that learning methods and learning styles have a significant effect on the learning outcomes of students at MI Roudlotul Mustashlihin Masangan Kulon, Sukodono, Sidoarjo. Effective learning methods are able to provide adequate learning experiences that suit students' learning styles, so they can increase understanding and acceptance of information. In addition, the suitability between the learning methods applied and students' learning styles can motivate them to be more active and participate in the learning process.